Social network aware content distribution scheme - De Guzman, Jaybie Agullo (College of Engineering, University of the Philippines Diliman, 2013)
The increasingly social activity of users in the Internet opens the probability that content distribution and delivery may benefit from an awareness of the underlying social nature and use such knowledge to optimize the placement and caching of content. Current algorithms and implementations of Content Delivery Networks do not use social information to enhance delivery. Observations on online social network traffic provided insights on how social information can be utilized for various network applications such as content delivery. To see the effects of social influence we performed various CDN implementations and observed the effect of using social influence in partitioning and distribution on the performance of these implementations over varying levels of social influence imposed in the traffic traces, and varying number of partitions. A proactive social-aware distribution scheme was developed that distributed content based on its popularity as well as the popularity of the users linked with the content through access. Implementations with this social aware content distribution did not provide a substantial improvement in the performance, but partitioning users based on the social graph showed a big performance improvement than the randomly patitioned implementation. Also, increasing number of partitions over a fixed population affects scattering of the users and content: degrading the overall performance of the CDN implementation. Although, the performance generally degrades with increasing scattering, social partitioning still shows improved performance than the other implementations.